2009
DOI: 10.1037/a0014412
|View full text |Cite
|
Sign up to set email alerts
|

Women's underrepresentation in science: Sociocultural and biological considerations.

Abstract: The underrepresentation of women at the top of math-intensive fields is controversial, with competing claims of biological and sociocultural causation. The authors develop a framework to delineate possible causal pathways and evaluate evidence for each. Biological evidence is contradictory and inconclusive. Although cross-cultural and cross-cohort differences suggest a powerful effect of sociocultural context, evidence for specific factors is inconsistent and contradictory. Factors unique to underrepresentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
573
3
12

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 799 publications
(633 citation statements)
references
References 370 publications
13
573
3
12
Order By: Relevance
“…In a related argument, Ceci et al (2009) claim that there are genuine gender differences in occupationa l preferenc es that reflect some mixture of ''free'' and ''constrai ned'' choices. The latter are best understo od as accommodati ons to beliefs, whether accurate or inaccurate, that some careers are more compatible than others with the biologica l exigencies of motherhood.…”
Section: Pipeline and Life Course Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a related argument, Ceci et al (2009) claim that there are genuine gender differences in occupationa l preferenc es that reflect some mixture of ''free'' and ''constrai ned'' choices. The latter are best understo od as accommodati ons to beliefs, whether accurate or inaccurate, that some careers are more compatible than others with the biologica l exigencies of motherhood.…”
Section: Pipeline and Life Course Modelsmentioning
confidence: 99%
“…The former reflect stable and deep-rooted differences between men and women in their preferences for particular types of tasks, but especially for caring, nurturing, and interactin g with people as opposed to objects. Ceci et al (2009) provide no new evidence in support of this essentiali st claim, but their interpretive review identifies ''pronounced sex differences in occupationa l preferenc es that occur along a 'people-to-obje ct' dimension (Lippa, 1998 ): Women are more likely to pursue people-oriented or organic fields, whereas men with similar mathematics and science ability tend to pursue object-orien ted fields (Webb et al, 2007 ;see Lippa, 2005 , for a review).'' The research reported in these citations 4 Not all STEM majors wind up in STEM occupations (see, e.g., Sassler et al, n.d.); and, conversely, some pathways into the science pipeline emerge late in educational careers (Xie and Shauman, 2003 ).…”
Section: Pipeline and Life Course Modelsmentioning
confidence: 99%
See 3 more Smart Citations